Parental leave policies and time use for mothers and fathers: a case study of Spain and Sweden. Issue 1 (1st January 2017) - Hagqvist, Emma; Nordenmark, Mikael; Pérez, Glòria; Trujillo Alemán, Sara; Gillander Gådin, Katja
ABSTRACT: States play an important role in gender equality through policy structuring. In this case study, the aim is to explore whether changes in parental leave policies over two decades trickle down to changes in gendered time use in two polarised countries: Sweden and Spain, represented by the Basque Country. Sweden represents dual-earner countries with high relative gender equality, whereas Spain represents a south European policy model supporting a breadwinning/homemaker ideal. The results show that changes in the gendered time use among mothers and fathers in both countries are associated with changes in parental leave policies. Changes in policies directed towards increasing gender equality reduce the gender gap in time use among mothers and fathers and seem to increase gender equality within a country. From these results, the conclusion is that parental leave policies that are structured to promote or enable gender equality could reduce the gender time gap in work among mothers and fathers.